Flight Control Design Considerations for Multicopters Operating in Adverse Atmospheric Conditions - Zumarraga, Augusto José (2018)
There is abundant literature related to the automatic control of multicopters showing the application of various control techniques, generally oriented to attitude control. This is one of the functions required for position and trajectory control, and is of greater academic interest due to its non-linear nature. However, it is not common to explore the conflicts that arise in the design when seeking to achieve high precision position control in adverse weather conditions. In this paper we analyze objectives, structural limitations and implementation needs that significantly impact the performance of a control system under these conditions. Some design criteria are proposed and the aptitude of a linear control scheme is evaluated to respond to these requirements. The development efforts are also discussed to achieve the required precisions in the estimation of position for an application of these characteristics.